Effects of probiotics on gut beneficial microbes in autistic children - Hathaichanok Kotchapetch (2020)
© 2019 IEEE. Objectives: To study the possible effects of probiotic on alteration the composition of gut beneficial microbes and gastrointestinal problem by using Bristol stool form scale (BSF scale) in autistic children before and after taking probiotic for 3 months. Research Methodology: The case of study refers to 13 autistic children with age 9 - 16 years old. Diagnosis of ASD according to DSM-V criteria. Single group, pre- and post-test study. Three multi-strain probiotics were taken once a day for 12 weeks. The markers included Bristol stool form scale (BSF scale) were collected on 0 and 6 weeks. Results: The probiotic treatment reduced the severity of gastrointestinal symptom.